Rozwój i wykorzystanie zasady poglądowości w edukacji matematycznej dzieci - Agnieszka Bojarska-Sokołowska (Problemy Wczesnej Edukacji)
The first part of the article presents the history of the development of the principle of viewpoints starting from its illustrative and static perception, and ending with its contemporary, interactive use. In the second part, referring to our own research, we describe and analyze the contemporary use of the principle of viewpoint during extracurricular mathematical classes organized for pre-school and younger school children. The essence of the contemporary use of the principle of objectivity is the intentional and skilful use of didactic means while shaping the mathematical concepts of students. Attention was paid to the fact that children were provided with conditions free and without time pressure to experiment with mathematical objects, the ability to agree their observations and discoveries with their peers, the teacher.